Influencia de hormonas de crecimiento sobre el desarrollo y rendimiento del cultivo de arroz (Oryza sativa L.)”. - Rodríguez Guayes, Adrián Olmedo (2018)
VII. SUMMARY The present experimental work was established in the lands of the CEDEGE Irrigation Project owned by Mr. Edison Javier Solarte Calero, located at Km 12 of the Babahoyo - Montalvo highway, between the geographical coordinates of 277438.26 UTM of West longitude and 110597, 97 UTM south latitude; with a height of 8 m.s.n.m. The zone presents a humid tropical climate, with an average annual temperature of 25.60 ° C, an annual rainfall of 2329.8 mm; relative humidity 82% and 998.2 hours of annual average heliophany. The soil is flat topography, loamy clay texture and regular drainage. We used certified seeds of the INIAP 16 rice variety. The objectives were to determine the agronomic behavior of rice to the treatments evaluated, indicate the best dose of the growth promoter alone and in a mixture and economically analyze the treatments according to the cost of production. . The treatments were evaluated with products based on growth hormones with doses / ha such as Cytokin 500 cc, Ergostim 500 cc, Phosphite potassium 500 cc, Phosphite magnesium 500 cc, Cytokin + Phosphite potassium 500 cc + 500 cc, Cytokin + Phosphite magnesium 500 cc + 500 cc, Ergostim + Phosphite potassium 500 cc + 500 cc, Ergostim + Phosphite magnesium 500 cc + 500 cc and Control treatment only with base fertilization. The experimental design of Complete Blocks at Random was used, with ten treatments and three repetitions. The mean comparisons were made with the Tukey multiple range test at 95% probability. The experimental plots had a diameter of 3.0 x 5.0 m, the separation between repetitions was 1.0 m, giving a test area of 550 m2. All the necessary agricultural work was done in rice cultivation for its normal development, such as land preparation, sowing, irrigation, fertilization, weed control, phytosanitary control, harvest. In order to correctly estimate the effects of the treatments, data were taken on the days of flowering and ripening, plant height at harvest, number of tillers and panicles, length of panicles, grains per panicle, grain-straw ratio, yield of the crop and economic analysis. Based on the results obtained, it was determined that the growth hormones positively influenced the development and yield of the rice crop; applying Phosphite magnesium in a dose of 500 cc / ha the crop flourished in less time, while with the use of Cytokin in a dose of 500 cc / ha it matured in less time; the highest plant height was recorded in the treatment that was applied Ergostim + Phosphite magnesium in doses of 500 cc + 500 cc / ha; the treatment that was used Ergostim + Phosphite potassium in doses of 500 cc + 500 cc / ha obtained greater number of tillers and panicles / m2, length of panicles and grains per panicles and the highest yield of the crop and net benefit was presented by the application of Ergostim + Phosphite potassium in doses of 500 cc + 500 cc / ha with $ 425.08.